Leber’s hereditary optic neuropathy – a case report - Roskal-Wałek, Joanna; Gierada, Magdalena; Mackiewicz, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Leber’s hereditary optic neuropathy (LHON) is a genetic disease caused by mitochondrial DNA mutations. Most patients with LHON have one of the three following point mutations in genes encoding for complex I of the mitochondrial respiratory chain: m.11778G>A, m.3460G>A, and m.14484T>C. Of these mutations, the 11778G>A mutation is the most common, and it is associated with the most severe disease course. Patients with the 11778G>A mutation may exhibit selective loss of retinal ganglion cells, which leads to optic nerve atrophy and, in most cases, bilateral loss of vision. We present a case of a patient with a sudden bilateral vision loss, who had the 11778G>A mutation.